Cash Waqf: Economic Solution during the Covid-19 Pandemic - Nurjannah Nurjannah; M.Wahyuddin Abdullah (IAIN Padangsidimpuan, 2020)
The emergence of the Covid-19 pandemic in Wuhan has made economies in various parts of the world experience instability. The real form that can be seen from the Covid-19 impact on the economy today is the Termination of Employment Relationship (PHK). Many employees have been dismissed, and various companies are even threatened with bankruptcy. Other aspects affected include casual daily laborers, MSME actors, restaurant businesses, and other businesses that involve large numbers of people. The type of study was qualitative. The researcher would explore an object to find the potential that existed in the object. This study used a library research method using secondary data obtained from articles, research results, and reference books that discussed the same topic as research. Cash waqf as Islamic financial philanthropy required the strengthening during the current pandemic to assist in the establishment of a Waqf Hospital (RSW), especially for COVID-19 victims, waqf Personal Protective Equipment (PPE), waqf masks, waqf polyclinic, Waqf Isolation House (RIW) and vaccine funding. Additionally, it could help micro business actors in funding for the sustainability of their businesses affected by the pandemic. If there were beneficiaries of cash waqf (al-mauquf alaih) who were not limited to religious provisions, there would equal distribution of aid to help slow economic recovery